A study on design principles and requirements for multimedia application development: MFolktales application for children's education - Ibrahim, N. (Institute of Electrical and Electronics Engineers Inc., 2016)
MFolktales is a multimedia application that contains Animation Module and interactivity modules which aim to promote Malay folk stories to children. This research is limited to children aged 5 to 7 years old. Therefore, approaches in developing animated multimedia applications are studied so that they can suit the children's interest and at the same time can act as a tool for learning. This paper discusses the study on design principles and requirements for multimedia application development which covers suitable learning theories, learning taxonomy, modules, user interface principles, and usability that are appropriate with the application developed. MFolktales application was developed based on the results of the study. This paper also provides some discussions regarding the guidelines utilized in developing the prototype. Finally, a set of usability questions was given to 30 parents who have children aged between 3 to 12 years old to evaluate the usability level of the developed prototype. The results showed that majority of the respondents gave a positive feedback on the developed MFolktales application. Â© 2015 IEEE.